Primary Prevention of Cervical Cancer: American Society of Clinical Oncology Resource-Stratified Guideline - Arrossi, Silvina (2017)
Purpose To provide resource-stratified (four tiers), evidence-based recommendations on the primary prevention of cervical cancer globally. Methods The American Society of Clinical Oncology convened a multidisciplinary, multinational panel of oncology, obstetrics/gynecology, public health, cancer control, epidemiology/biostatistics, health economics, behavioral/implementation science, and patient advocacy experts. The Expert Panel reviewed existing guidelines and conducted a modified ADAPTE process and a formal consensus-based process with additional experts (consensus ratings group) for one round of formal ratings. Results Existing sets of guidelines from five guideline developers were identified and reviewed; adapted recommendations formed the evidence base. Five systematic reviews, along with cost-effectiveness analyses, provided evidence to inform the formal consensus process, which resulted in agreement of ‡ 75%. Recommendations In all resource settings, two doses of human papillomavirus vaccine are recommended for girls age 9 to 14 years, with an interval of at least 6 months and possibly up to 12 to 15 months. Individuals with HIV positivity should receive three doses. Maximal and enhanced settings: if girls are age ‡ 15 years and received their first dose before age 15 years, they may complete the series; if no doses were received before age 15 years, three doses should be administered; in both scenarios, vaccination may be through age 26 years. Limited and basic settings: if sufficient resources remain after vaccinating girls age 9 to 14 years, girls who received one dose may receive additional doses between age 15 and 26 years. Maximal, enhanced, and limited settings: if ‡ 50% coverage in the priority female target population, sufficient resources, and cost effectiveness, boys may be vaccinated to prevent other noncervical human papillomavirus–related cancers and diseases. Basic settings: vaccinating boys is not recommended. It is the view of the American Society of Clinical Oncology that health care providers and health care system decision makers should be guided by the recommendations for the highest stratum of resources available. The guideline is intended to complement but not replace local guidelines.